Muscular fitness comparison among different racquet sports / Muhammad Firdaus Mohd Sazali - Mohd Sazali, Muhammad Firdaus (2019)
The purpose of this study is to investigate muscular fitness comparison among different racquet sports, which are badminton, tennis & squash. A total of thirty subjects (N=30) from 3 racquet sports category from Universiti Kebangsaan Malaysia (UKM) were selected through purposive sampling. The study compared the muscular fitness components among racquet sports. One way ANOVA was used as this study will compare 3 tests given among 3 different racquet sports. Based on ANOVA, the result showed there was no significant difference between muscular fitness tests and 3 different racquet sports, since p-value are more than 0.05, which is handgrip test among different racquet sports were (p = 0.12), push-up test among different racquet sports were (p = 0.39) and bench press test among different racquet sports were (p = 0.44). To conclude, this finding suggests that muscular fitness tests comparison does not give any significant difference among different racquet sports.